2020
DOI: 10.1007/s00249-020-01459-4
|View full text |Cite
|
Sign up to set email alerts
|

Albumin displacement at the air–water interface by Tween (Polysorbate) surfactants

Abstract: Tween (polysorbate) 20 and 80 are surfactants used for the development of parenteral protein drugs, due to their beneficial safety profile and stabilisation properties. To elucidate the mechanism by which Tween 20 and 80 stabilise proteins in aqueous solutions, either by a “direct” protein to surfactant interaction and/or by an interaction with the protein film at the air–water interface, we used spectroscopic (Infrared Reflection Absorption Spectroscopy, IRRAS) and microscopic techniques (Brewster Angle Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…For another example, let us consider a liquid formulation of an antibody that contains a surfactant to cover the solution−air and solution−container interfaces in order to avoid the surface-induced denaturation of the protein. 36 For a singlecomponent surfactant, surface coverage would remain unchanged as long as the surfactant concentration remains above the cmc. Within this range, the surfactant concentration can be optimized according to other considerations (viscosity, interactions with other excipients, etc.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%
“…For another example, let us consider a liquid formulation of an antibody that contains a surfactant to cover the solution−air and solution−container interfaces in order to avoid the surface-induced denaturation of the protein. 36 For a singlecomponent surfactant, surface coverage would remain unchanged as long as the surfactant concentration remains above the cmc. Within this range, the surfactant concentration can be optimized according to other considerations (viscosity, interactions with other excipients, etc.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%
“…On one hand, although little is known about the functionality of specific isolated PS fractions, this variety might be the key to the beneficial and stabilizing properties of PS. On the other hand, the heterogeneity leads to different susceptibilities to degradation of the individual components during storage in pharmaceutical formulations ( Grabarek et al, 2020 ; Khan et al, 2015 ; Rabe et al, 2020 ; Nayem et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These three components were dispersed in an aqueous environment to form the NLC structure (Figure a). Because T80 has a large hydrophilic head group, it is located at the interface and stably disperses particles. , In addition, T80 has an octanol–water partition coefficient (Log P = 4.8) that is less than that of the other components (Figure a, table), implying that T80 is mainly distributed in the region close to the aqueous phase. Our previous study identified the dependence of self-assembly behavior on the NLC composition, including the surfactant concentration .…”
Section: Resultsmentioning
confidence: 99%